Internal Endoconduit Technique during Transcatheter Aortic Valve Implantation - Sakai, Osamu; Oka, Katsuhiko; Inoue, Tomoya; Yaku, Hitoshi (The Thoracic and Cardiovascular Surgeon Reports, 2019)
The transfemoral approach is the least invasive transcatheter aortic valve implantation (TAVI) approach, but the diameter of the iliofemoral arteries needs to exceed 5 mm. We report a case of limited access transfemoral TAVI by the “internal endoconduit technique,” which is well known as a safe and effective dilatational technique for thoracic endovascular aortic repair. Subsequently, we could deliver the device without iliac artery injury and we performed transfemoral TAVI.
Keywords: valvular surgery; aortic valve; TAVI; peripheral vascular disease